3.38 kW all-fiberized narrow linewidth fiber laser based on active polarization control using RMS-Prop algorithm - Ren, Shuai; Chang, Hongxiang; Ma, Pengfei; Chen, Yisha; Wang, Guangjian; Li, Wei; Liu, Wei; Yao, Tianfu; zhou, Pu (Optics and laser technology, 2023)
•Root-Mean-Square propagation (RMS-prop) algorithm is developed and first employed in polarization control technique.•Experimental research is conducted for polarization control of non-PM narrow linewidth fiber laser with high output power.•As far as we know, this is the first time to realize over 3 kW linearly polarized fiber laser based on polarization control. Active polarization control in high power narrow linewidth non-polarization maintained (non-PM) fiber amplifier is investigated in this paper. The non-PM fiber laser is realized employing bidirectional pump configuration seeded with narrow linewidth laser source. Root-Mean-Square propagation (RMS-prop) algorithm is developed and first employed in polarization control technique. When control system does not work, the polarization extinction ratio (PER) of output signal laser varies between 0.25 dB and 4.61 dB. When control system works, the PER stably remains above 12.2 dB during power amplification. At laser power of 3.38 kW, the PER is 12.2 dB, 3 dB linewidth is measured to be ∼0.32 nm, and beam quality (M2 factor) is M2x = 1.39, M2y = 1.50. This is the first time to realize over 3 kW linearly polarized fiber laser based on active polarization control to the best of our knowledge.